Public Interaction of Web Self-Presentation - Elena Junova (Communications - Scientific letters of the University of Zilina, 2014)
The article is focused on a specific area of copywriting - self-presentation of companies on the websites . It analyzes 190 webpages of smaller companies and 190 webpages of larger companies, compares their presentations and points out differences. The adaptation of the text to the search engine optimization and to the target audience and other aspects which create the specificity of copywriting are discussed.